2017
DOI: 10.1016/j.chiabu.2017.01.019
|View full text |Cite
|
Sign up to set email alerts
|

Rethinking research on sexual exploitation of boys: Methodological challenges and recommendations to optimize future knowledge generation

Abstract: Research and policies on child and adolescent sexual exploitation frequently focus on the sexual exploitation of girls and fail to recognize the experiences of sexually exploited boys, including their potentially unique health care and social support needs. This oversight limits the ability of health care and social service providers to offer both targeted and evidence informed care to sexually exploited boys. As a first step in a larger grant to understand the experiences of sexually exploited boys and to dev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
28
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 30 publications
1
28
0
2
Order By: Relevance
“…The studies confirmed earlier research indicating that boys are an important part of adolescents selling sex, which is often in opposition to the general awareness within society (Kaestle, 2012;McNeal & Walker, 2016;Mossige et al, 2007;Moynihan et al, 2018;Pedersen & Hegna, 2003;Svedin & Priebe, 2007). Further, Study II might help us to understand the gender bias that has been seen in the existing literature regarding adolescents selling sex, where boys are seldom seen in clinical samples (Mitchell et al, 2017;Moynihan et al, 2018). Study II found that there is a difference between boys and girls concerning selfreported motives for selling sex.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The studies confirmed earlier research indicating that boys are an important part of adolescents selling sex, which is often in opposition to the general awareness within society (Kaestle, 2012;McNeal & Walker, 2016;Mossige et al, 2007;Moynihan et al, 2018;Pedersen & Hegna, 2003;Svedin & Priebe, 2007). Further, Study II might help us to understand the gender bias that has been seen in the existing literature regarding adolescents selling sex, where boys are seldom seen in clinical samples (Mitchell et al, 2017;Moynihan et al, 2018). Study II found that there is a difference between boys and girls concerning selfreported motives for selling sex.…”
Section: Discussionsupporting
confidence: 80%
“…However, there are currently few studies concerning male adolescents selling sex, giving a strong female bias in the literature investigating adolescents selling sex (Mitchell et al, 2017).…”
Section: Male Prostitutionmentioning
confidence: 99%
“…While conducting a previous systematic review of sexually exploited boys (Mitchell et al, 2017), we found including the MeSH term "child sexual abuse" generated thousands of results not relevant to child and adolescent sexual exploitation, such as nonspecific abuse and incest. Thus, we piloted database searches that both included and excluded the MeSH term "child sexual abuse."…”
Section: Methodsmentioning
confidence: 99%
“…(Beckett et al ., , p. 7)This definition has been chosen because it highlights that CSE is one form of child sexual abuse among others, like intra‐familial child sexual abuse and harmful sexual behaviour carried out by children against other children. However, it is important to note that definitions of CSE are contested and different jurisdictions may use terminology associated with human trafficking rather than with child sexual abuse, which may result in inconsistent policy and practice responses to the problem (Brayley and Cockbain, ; Mitchell et al ., ).…”
Section: Introductionmentioning
confidence: 97%